DISTRIBUTION OF WITHIN-RING INTERNAL CHECKING IN Pinus Radiata GROWN IN SOUTHERN CHILE - A. Aguilera (Maderas. Ciencia y Tecnología, 2009)
The increase of Pinus radiata plantations in Chile has brought larger annual volumes to the industry and the opportunity to process them into value-added products. Within-ring checks constitute an important problem that may affect the appearance quality of lumber. This problem occurs in the early wood portion of sapwood growth rings in dry lumber and can only be seen when the board is cross cut. The purpose of this study was to analyze the frequency of within-ring internal checking in kilndried Pinus radiata lumber from different logs grown in southern Chile. Centre boards were more affected by the internal checking. Checks were located more frequently between rings 4 to 6.